Morphology and distribution of pelagic ostracods of the genus Boroecia (Ostracoda: Halocyprididae) in the Central Arctic - Chavtur, Vladimir G.; Keyser, Dietmar A. (Zootaxa, 2015)
Morphologically similar Boroecia borealis and B. maxima are redescribed from the Central Arctic. Their morphological differences are minor but well defined. Their geographic and vertical distribution is studied based on an extensive body of materials collected by many expeditions in the Arctic Ocean during the period from 1929 to 1993 at the depth range of 0–4000 m. The comparison of the distribution of both species reveals that B. borealis prefers waters of subarctic structure in the Atlantic, and it inhabits waters in the relatively warm Atlantic layer in the Arctic. In contrast, B. maxima is a good indicator of cool Arctic waters. This species is also present in greater depths of the Northern Atlantic, where polar waters penetrate far towards the south.